Influence of longitudinal radiation exposure from microcomputed tomography scanning on skeletal muscle function and metabolic activity in female CD‐1 mice. Issue 13 (4th July 2017) - Mikhaeil, John S.; Sacco, Sandra M.; Saint, Caitlin; Gittings, William; Bunda, Jordan; Giles, Cameron R.; Andrew Fajardo, Val; Vandenboom, Rene; Ward, Wendy E.; LeBlanc, Paul J.
Abstract: Microcomputed tomography ( μ CT) is an imaging technology to assess bone microarchitecture, a determinant of bone strength. When measured in vivo, μ CT exposes the skeletal site of interest to a dose of radiation, in addition to nearby skeletal muscles as well. Therefore, the aim of this study was to determine the effects of repeated radiation exposure from in vivo μ CT on muscle health – specifically, muscle morphometrics, contractile function, and enzyme activity. This study exposed the right hind limb of female mice to either a low (26 cGy) or moderate (46 cGy) dose, at 2, 4, and 6 months of age, while the left hind limb of the same animal was exposed to a single dose at 6 months to serve as a nonirradiated control. Muscle weight, cross‐sectional area, isometric contractile function, and representative maximal enzyme activities of amino acid, fatty acid, glucose, and oxidative metabolism in extensor digitorum longus (EDL) and soleus were assessed. Low‐dose radiation had no effect. In contrast, moderate‐dose radiation resulted in a 5% increase in time‐to‐peak tension and 16% increase in half‐relaxation time of isometric twitches in EDL, although these changes were not seen when normalized to force. Moderate‐dose radiation also resulted in an 33% decrease in citrate synthase activity in soleus but not EDL, with no changes to the other enzymes measured. Thus, three low doses of radiation over 6 months had no effect on contractile function or metabolic enzyme activity in soleus and EDL of female mice. In contrast, three moderate doses of radiation over 6 months induced some effects on metabolic enzyme activity in soleus but not EDL. Future studies that wish to investigate muscle tissue that is adjacent to scanned bone should take radiation exposure dose into consideration. Abstract : Our data demonstrate that repeated radiation exposure at two different doses (26 and 46 cGy), commonly used to image bone structure, from microcomputed tomography ( μ CT) did not alter soleus or extensor digitorum longus (EDL) morphometrics (weight and cross‐sectional area), in vitro contractile function, and most enzyme activities measured in female mice. One exception is exposure to 46 cGy resulted in a lower maximal citrate synthase activity in soleus, but not EDL. Thus, longitudinal μ CT scanning to provide sufficient quality bone images should take radiation dose into consideration to not impact neighboring muscles.